Association between growth differentiation factor 15 and left ventricular hypertrophy in hypertensive patients and healthy adults. (2nd January 2018) - Kou, Huijuan; Jin, Xin; Gao, Dengfeng; Ma, Rui; Dong, Xin; Wei, Jin; Wang, Xin
ABSTRACT: Growth differentiation factor 15 (GDF-15) as an independent biomarker of cardiovascular diseases merits further evaluation. We studied the association between plasma GDF-15 levels and left ventricular hypertrophy (LVH) in hypertensive patients and healthy adults. Hypertensive LVH measurements were performed via echocardiography and analyzed using the cube formula, and human GDF-15 together with interleukin-6 (IL-6) and matrix metalloproteinase-9 (MMP-9) concentrations were determined via enzyme-linked immunosorbent assay (ELISA). All data were analyzed using SPSS 13.0 software. A total of 302 participants were recruited for this clinical study. Circulating GDF-15, IL-6 and MMP-9 levels were significantly higher in LVH patients ( n = 67) than in non-LVH patients ( n = 172) and healthy controls ( n = 63) ( p < 0.001). After adjustment for confounders via multivariate logistic regression, elevated plasma GDF-15 concentrations remained independently associated with LVH in hypertensive patients. In addition, GDF-15 was positively correlated with IL-6 and MMP-9 levels in human plasma, respectively, suggesting that a link exists between GDF-15 expression and inflammation. We also calculated an optimal GDF-15 cut-off point with which LVH severity can be predicted in the current study. In conclusion, GDF-15 is associated with hypertensive LVH and may be a powerful biomarker with which LVH risk can be predicted in patients with hypertension.